Determination of Priority Sectors in Economic Development in Maluku Province - Nikijuluw, Jeanee Belthia (Jurnal Multidisiplin Madani, 2024)
This research aims to determine priority sectors in formulating economic development policies in Maluku Province. The methods used in this research are Location Quotient (LQ), Shift Share (SS), and Klassen Typology. The research results show that based on the three methods above, the priority sectors in economic development in Maluku Province are sectors that have superiority, and competitiveness and are among advanced and rapidly developing sectors (prime sectors). These sectors are the Agriculture, Forestry, and Fisheries sectors, the Wholesale and Retail Trade sector, Car and Motorcycle Repairs, the Government Administration, Defense and Mandatory Social Security sectors, and the Education Services sector. This sector is a sector that absorbs a lot of workers. Apart from that, the primary sector is a sector that plays an important role in economic development in Maluku Province. The contribution of the agriculture, forestry, and fisheries sectors indirectly shows that the economic structure of Maluku province is still supported by the traditional economy. Then, geographically, the vast area of Maluku Province, the majority of which is water areas; however, this sub-sector has yet to become the main support for the economy of Maluku Province. For this reason, the Maluku provincial government should prioritize the superior sectors and commodities it owns while still paying attention to other industries and commodities according to their potential and development opportunities in order to encourage the growth of Maluku Province's GRDP for future regional development. The implications of this research can be recommendations for economic planning and development in Maluku Province. The implications of this study can be recommendations for economic planning and development in Maluku Province